Determination of anisotropy and multimorphology in fly ash based geopolymers - Khan, M.I. (American Institute of Physics Inc., 2015)
In this study, Malaysian coal fly ash-based geopolymers were investigated for its morphology and chemical composition using scanning electron microscopy coupled with energy dispersive X-rays (SEM-EDX). Geopolymer was synthesized using sodium hydroxide as activator. SEM studies revealed multiphasous structure of the material, composed of geopolymeric gel, partially reacted fly ashparticles and selectively leached particles. EDX analysis confirmed the chemical composition of different regions. Infra red spectroscopic studies supported the SEM-EDX analysis by confirming presence of unreacted quartzite and mullite in geopolymers. It is concluded that geopolymers possese a non uniform chemistry through out the structure. Â© 2015 AIP Publishing LLC.